Good Corporate Governance Memoderasi Pengaruh Leverage Terhadap Manajemen Laba - Yudiastuti, Luh Nopia; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi, 2018)
The profit information that is a component of the financial statements has a very important potential for both internal and external parties. The profit information that is part of the financial statements is often the target of management to maximize its personal interests. Improvement of corporate management is needed to suppress the fraud committed by the management, one of which is applying the concept of Good Corporate Governance (GCG) within the company. This study aims to obtain empirical evidence about the influence of leverage on earnings management with Good Corporate Governance (GCG) as a moderator. This research was conducted at the nonfinancial company following the CGPI score in a row from 2011-2015 and listed on the Indonesia Stock Exchange. The method which is used in this research is Moderated Regression Analysis. The result of research, it is known that leverage has no effect on earnings management. The study also found that GCG is unable to moderate the effect of leverage on earnings management. Keyword: earnings management, leverage, good corporate governance